CONFIGURAÇÕES E TENDÊNCIAS DAS RÁDIOS COMUNITÁRIAS DO INTERIOR PAULISTA DA REGIÃO DE BAURU - Volpato, Marcelo de Oliveira (2010)
This research provides a mapping of the main trends and characteristics involving the 23 legal community radio stations active in Administrative Region of Bauru, located in Brazil´s state of São Paulo. Its objective was to understand how they relate to the local population, the way they operate, their management models, the circumstances in wich they were licensed, as well as discussing whether and how they enable popular participation and contribute do the expansion of citizenship. Guiding parameters for the analysis of such radio stations were defined from the discussion of concepts like "community", local" and "region", sought to enumerate the characteristics usually found (and those who ideally could be expected) in community, local and regional media, especially regarding the aspects of popular participation and citizenship. The study of multiple cases combined to bibliographical research was adopted as methodology of research. The techniques used consisted of interviews with the managers of the radio stations, study of documents and observation of their programming. The research revealed a complex, flexible and contingent universe, where the contribution to the promotion of citizenship is very much dependent on the managers intentions, availability and focus. Even so, and despite all their limitations, such radio stations represent a step forward in the democratization of communication in Brazil, especially in places where there is no other locally-based options available.(AU)